SOSIALISASI PEMANFAATAN LIMBAH DAUN SAGU SEBAGAI BAHAN BAKU BRIKET ARANG KEPADA MASYRAKAT NEGERI URENG KABUPATEN MALUKU TENGAH - Siruru, Herman; Tan, Lieke; Liliefna, Leonard Dantje; Imlabla, Nancy Wilma; Hutabarat, Lasti Patresia; Samosir, Agustinus Hasiholan; Pereira, Evangelino Martinho; Narahawarin, Desi (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Sago leaves are one of the biomass potentials that contain cellulose so that they can be used as raw materials for charcoal briquettes. The purpose of community service activities is to increase community knowledge so that they can utilize biomass potential as an alternative energy source. The stages of activities in implementing PKM activities are a social approach to the Ureng Village government one month before the PKM activity date. PKM activities are carried out in two sessions, namely: delivery of materials and practice of making charcoal briquettes starting from carbonization of sago leaves, making charcoal briquettes and utilizing charcoal briquettes by burning sago leaf charcoal briquettes. This activity went well because the people of Ureng Village were very enthusiastic, this was reflected when building a dialogue in the form of questions related to how to make charcoal briquettes.